2015
DOI: 10.2174/1874350101508010133
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Telephone Help-lines by Lonely Children and Adolescents

Abstract: Loneliness is a subjective distressing feeling of being disconnected from a desired group or intimate relationship. Most children and adolescents experience loneliness at some time but for 10-20% of young people it can be severe and chronic. While there are many avenues for help for distressed young people, such as friends and family as well as the professional help of counselors and psychologists, lonely young people often do not seek help. Telephone help-lines are one way to assist young people in difficulty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Campbell (2015) reported that children aged 7-12 years seek help from others about their experience of loneliness. Campbell (2015) reported that children aged 7-12 years seek help from others about their experience of loneliness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Campbell (2015) reported that children aged 7-12 years seek help from others about their experience of loneliness. Campbell (2015) reported that children aged 7-12 years seek help from others about their experience of loneliness.…”
Section: Resultsmentioning
confidence: 99%
“…Help‐seeking depends upon age and gender. Campbell () reported that children aged 7–12 years seek help from others about their experience of loneliness. As a form of coping, it appears to decline with ages.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the proliferation of societal attempts to help the lonely, telephone help lines are now spread throughout the world. Campbell [9] provided a comprehensive review of the telephone help lines dedicated to helping the youth, and the reasons that children and adolescents do not take full advantage of that readily available extended hand. [10] attended to the loneliness experienced by first year college and university students, loneliness and other related emotions that may hamper their academic achievements.…”
Section: Addressing Lonelinessmentioning
confidence: 99%
“…For example, shame from the social stigma of mental illness is common and can interfere with individuals utilizing crisis phone lines ( Gould et al, 2006 ). Placing a greater value on self-reliance ( Gould et al, 2006 ) and concerns about anonymity ( Campbell, 2015 ) are also associated with a lower likelihood of reaching out to telephone hotlines. Despite high rates of mental illness among adolescents, uptake is limited in this population ( Evans et al, 2013 ), with one study indicating that only 2.1% of adolescents use crisis hotlines ( Gould et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%